Timothy of the cay - Taylor, Theodore, 1921-2006. (New York : Avon, 1994)
Having survived being blinded and shipwrecked on a tiny Caribbean island with the old black man Timothy, twelve-year-old white Phillip is rescued and hopes to regain his sight with an operation.
Elem. School Library Collection.
Wilson's Children.
Wilson's Junior High School.
6.1
5-8
Keywords: Shipwrecks -- Fiction; Survival -- Fiction; Shipwrecks -- Fiction; Survival after airplane accidents, shipwrecks, etc. -- Fiction; Caribbean Area -- Fiction; Caribbean Area -- Fiction